POTENCIALIDADES DO PARQUE DA CIDADE EM SERRA-ES PARA O ENSINO DE BOTÂNICA: UMA PROPOSTA DE SEQUÊNCIA DIDÁTICA (Revista Eletrônica Debates em Educação Científica e Tecnológica, 2021)
With the object of elaborating a didactic sequence that shows the educational potential of the Parque da Cidade (Park of the City) in Serra - ES, for the teaching of botany, by experiences of education through the formal and non-formal spaces of education was developed. It was a qualitative research, of the type of study of case. The research was divided into three stages: The first step was to raise the potential of the Parque da Cidade for the teaching of botany in basic education, at perspective of formal and nonformal education. The second was to elaborate a sequence didactic about Botany, through educational experiences that permeate the formal and non-formal spaces of education; and the third was to validate priority the sequence didactic with pairs. The validation was performed by eight teachers of different disciplines of basic education. It is expected that the didactic sequence may contribute to improving the dynamics of botany classes, motivating the teacher differentiated forms of explanation of this content in the classroom and that students understand content more effectively, assimilating it easily and associating it with your daily routine.
Keywords: Botany Teaching; Non-formal Education; Sequence Didactic